The ECI guide to managing health in construction - Gibb, Alistair G. F.; Gyi, Diane E.; Thompson, Trevor (Thomas Telford, 1999)
'The ECI Guide to Managing Health in Construction' has been written for site managers, helath and safety managers, and other managers with a responsibility or interest in the management of health in the construction industry.
Keywords: Construction industry -- Employees -- Health and hygiene -- Management.; Construction industry -- Health aspects -- Handbooks, manuals, etc.; elektronické knihy; electronic books